IEEE INFOCOM 2020 - IEEE Conference on Computer Communications 2020
DOI: 10.1109/infocom41043.2020.9155464
|View full text |Cite
|
Sign up to set email alerts
|

When FTM Discovered MUSIC: Accurate WiFi-based Ranging in the Presence of Multipath

Abstract: The recent standardization by IEEE of Fine Timing Measurement (FTM), a time-of-flight based approach for ranging has the potential to be a turning point in bridging the gap between the rich literature on indoor localization and the so-far tepid market adoption. However, experiments with the first WiFi cards supporting FTM show that while it offers meter-level ranging in clear line-of-sight settings (LOS), its accuracy can collapse in non-line-of-sight (NLOS) scenarios. We present FUSIC, the first approach that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…FUSIC [26] is based on ToF measurements to determine the device position. It relies on FTM ranging and uses the 1-dimensional MUSIC algorithm to reduce multipath effects.…”
Section: Comparison With Other Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…FUSIC [26] is based on ToF measurements to determine the device position. It relies on FTM ranging and uses the 1-dimensional MUSIC algorithm to reduce multipath effects.…”
Section: Comparison With Other Systemsmentioning
confidence: 99%
“…Estimating the absolute ToF and thus the distance between client and AP requires timestamped packet exchanges, as standardized in the 802.11 Fine Timing Measurement (FTM) protocol [23,24]. However, FTM is inaccurate in multipathrich environments [26]. UbiLocate uses a custom protocol similar to FTM that has lower overhead and is more robust by decomposing the multipath channel to accurately determine the ToF of the first path.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain studies investigated methods to improve the ranging accuracy using both RSS and RTT measurements [33], [37] or multiple RTT measurements obtained from different frequency bands [44]. Moreover, a high-resolution estimation technique was proposed to improve the ranging accuracy when the CSI of FTM packets is available [42]. In the positioning stage, Bayesian filtering techniques have been applied to track the location of mobile devices using a series of ranging results.…”
Section: Introductionmentioning
confidence: 99%
“…However, the FTM protocol is known to produce biased ranging outputs, which must be calibrated to achieve accurate ranging and positioning performances. Furthermore, some papers indicated that the FTM protocol generates a higher number of ranging errors in non-line-of-sight (NLOS) conditions than that in line-of-sight (LOS) conditions [42], [47]. In this situation, this work studies a machine learning-based approach to obtain precise ranging results.…”
Section: Introductionmentioning
confidence: 99%